The European Commission and EUA prices: a high-frequency analysis of the EC's decisions on second NAPs - Waldemar Rotfuß; Christian Conrad; Daniel Rittler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper empirically examines price formation in the European Union Emissions Trading Scheme (EU ETS). Our analysis shows that unexpected allocations of European Union Allowances (EUAs) lead to pronounced price reactions of the expected signs. Moreover, we find evidence that the adjustment of EUA prices to the European Commission's decisions on second National Allocation Plans (NAPs) is not instantaneous, but takes up to six hours after the decision announcement.
Keywords: G13; G14; G15; G17; G19; Q4; Q5; 330; EU ETS; price formation; European Union Allowance (EUA); European Commission; Emissionsrechte; Preis; Allokation; EU-Umweltpolitik; Ankündigungseffekt; EU-Staaten